Strategic Agility and Firm Performance: A Test of Dynamic Capabilities in a Turbulent Environment - Ramadhan, Ahmad Fauzan; Anindya, Siti Rahmawati (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2026)
A tumultuous business environment powered by technological disruption, market volatility, and fierce competition necessitates companies to implement adaptive strategies. This study examines the impact of strategic agility on firm performance, using dynamic capability as the primary theoretical lens. A quantitative method was used via an explanatory survey of 200-300 managers from medium and large-scale companies operating in highly uncertain sectors. Information was gathered through structured questionnaires and analyzed using variance-based Structural Equation Modeling (SmartPLS). The findings show that dynamic capability has a significant impact on strategic agility, and that strategic agility has a significant impact on firm performance. The performance impact of dynamic capability remains strong, but it is strongest when it passes through the strategic agility mediator. The argument is that the capabilities of sensing, seizing, and reconfiguring lead to performance only if they are communicated to management as enabling fast, flexible decision-making. The present research aims to clarify the role of strategic agility as a critical channel linking dynamic capability to firm performance, and, secondly, to provide managers with practical implications for developing adaptive strategies to secure sustainable performance in an ever-changing business climate.